Duplicity - Roberts, Julia; Owen, Clive; Giamatti, Paul.; Wilkinson, Tom.; Mccarthy, Thomas ([United States] : Universal, 2009)
Two sexy spies turned corporate operatives attempt to pull off one of the biggest heists ever. As the stakes rise in the ultimate game of cat and mouse, they'll put everything on the line to remain one double-cross ahead of the rest.
"The movie resembles 'Mad' magazine's Spy vs. Spy series, elevated to labyrinthine levels of complexity."--Roger Ebert, Chicago Sun-Times.
"The look and sound of 'Duplicity' is half the payoff."--Michael Phillips, Chicago Tribune.
"Superior entertainment, the most elegantly pleasurable movie of its kind to come around in a very long time."--New York Times.
"Whip-smart, sexy and delightfully twisty romantic thriller."--New York Post.
Julia Roberts, Paul Giamatti, Thomas Mccarthy, Tom Wilkinson, Clive Owen.
Rated PG-13.
DVD.
English, French, Spanish audio; French, Spanish subtitles.